Case report: Cutaneous metastasis of squamous cervical carcinoma: complete regression after molecular diagnosis - Liwen Guo; Yanqiong Liu; Shuhua Zhang; Wei Liu; Wei Liu (Frontiers in Immunology)
Common metastasis sites for cervical cancer are the lungs, bones, liver, brain, ovaries, and lymph nodes, among other sites. Skin metastasis is very uncommon, and is only observed in approximately 1% of patients. The cancer spreads typically through lymphatic or blood vessels, but a definitive example of lymphatic spread has not been documented thoroughly in the existing literature. Cutaneous metastasis may be confused with cellulitis or a rash; hence, an immediate cutaneous biopsy of any suspicious lesions is recommended. There is no consensus regarding the treatment of this condition. Only one documented case has shown that a combination of paclitaxel, carboplatin, bevacizumab, and zoledronic acid can lead to a complete metabolic response. Our study, which used two cycles of albumin-bound paclitaxel, cisplatin, and bevacizumab, followed by four cycles of the same regimen plus terprelimab for metastases with CPS scores of Programmed death-ligand 1 (PD-L1) over 10, resulted in a stable complete response for over eight months. Our contribution may assist in formulating effective treatment guidelines for the cutaneous metastasis of squamous cervical carcinoma in the future.